Fixed exchange rate regimes, real undervaluation and economic growth - Rui Mao; Yang Yao (Bank of Finland, Institute for Economies in Transition (BOFIT), 2015)
This paper empirically studies how a fixed exchange rate regime (FERR) may promote economic growth by undermining the Balassa-Samuelson effect. When total factor productivity (TFP) is faster in the industrial sector than in the non-tradable sectors, an FERR can suppress the Balassa-Samuelson effect if adjustment of domestic prices is subject to nominal rigidities. With WDI data on sectoral value-added and data from the PPP converter provided by the Penn World Table, we are able to estimate the home country's industrial-service (quasi-) relative-relative TFP in comparison with the United States. Applying those esti-mates, our econometric exercises then provide robust results that an FERR dampens the Balassa-Samuelson effect and that the real undervaluation that ensues does indeed promote growth. We also explore the channels for undervaluation to promote growth. Lastly, we compare industrial countries and developing countries and find that an FERR has more significant impacts on developing countries than on industrial countries.
URN:NBN:fi:bof-201508181360
Keywords: F31; F43; O41; 330